2005
DOI: 10.1053/j.jvca.2005.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Analgesia or Intravenous Morphine Analgesia After Thoracoabdominal Esophagectomy: A Prospective Follow-up of 201 Patients

Abstract: No differences in morbidity/mortality rates depending on analgesic treatment were observed in patients undergoing thoracoabdominal esophagectomy. Thoracic epidural analgesia provided better pain relief with fewer opioid-related side effects than intravenous morphine analgesia. However, postoperative epidural analgesia was associated with more technical difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 44 publications
(12 reference statements)
0
33
0
Order By: Relevance
“…30 A group of authors examined the effect of thoracic epidural bupivacaine-morphine versus IVPCA morphine after thoracoabdominal esophagectomy. 31 Pain scores at rest and with mobilization were better in the epidural group on postoperative day 1, as were the opioid-mediated side effects such as sedation. It was noted, however, that one third of those in the epidural group had their infusion discontinued earlier than planned because of technical failures such as insufficient analgesia or catheter displacement.…”
Section: Methods Of Pain Control In the Intensive Care Unitmentioning
confidence: 87%
“…30 A group of authors examined the effect of thoracic epidural bupivacaine-morphine versus IVPCA morphine after thoracoabdominal esophagectomy. 31 Pain scores at rest and with mobilization were better in the epidural group on postoperative day 1, as were the opioid-mediated side effects such as sedation. It was noted, however, that one third of those in the epidural group had their infusion discontinued earlier than planned because of technical failures such as insufficient analgesia or catheter displacement.…”
Section: Methods Of Pain Control In the Intensive Care Unitmentioning
confidence: 87%
“…The use of thoracic epidural analgesia in the context of esophagectomy has been shown to reduce the incidence of postoperative sedation [42]. Therefore, maintenance of homeostasis is an important cornerstone of prevention of postoperative complications.…”
Section: Prevention and Prophylaxismentioning
confidence: 99%
“…The use of neuraxial analgesia is associated with better relief of pain and fewer opioid-related side effects. 8,38 This results in a reduction in the need for postoperative ventilation. 39 Furthermore, Rigg et al 40 have reported a positive influence of epidural analgesia on the outcome of major abdominal surgery.…”
Section: How Can the Analgesic Strategy Influence Patient Tolerance Wmentioning
confidence: 99%